PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA PT. KABELINDO MURNI Tbk - Mukti Aji, Lintang Pamugar; Kristiani, Endah (ITB AAS Indonesia Surakarta, 2023)
This study aims to examine the effect of work discipline, work environment and training on employee productivity. The number of samples used in this study amounted to 104 employees using a saturated sampling technique. The data collection method used is a questionnaire. Data analysis used descriptive analysis, multiple linear regression analysis and partial coefficient of determination with SPSS version 21. The results of the study showed that work discipline, work environment and training had a positive and significant effect on employee productivity. The researcher concludes that with good discipline, a comfortable work environment and good service quality will increase employee work productivity. Suggestions given by researchers in order to maintain or increase work productivity, organizations need to maintain or improve discipline, work environment and the quality of training provided to employees to help achieve organizational goals. Keywords : Work Discipline, Working Environment, Training, Work Productivity